Dementia, Islamic indication and scientific evidence - Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Nordin, Mohamad Sahari; Ab Rahman, Jamalludin; Md Aris, Mohd Aznan; Rathor, Mohammad Yousuf; Abdur Rashid, Mohammad (Centre for Promoting Ideas, USA, 2011)
Background: The increasing prevalence of dementia has dramatic effects on lives of millions of people across the regions and on public health costs. This is a commonly elderly health health problem as indicated in the Holy Qur’an. Although there is no cure yet but much can be done to improve the quality of life of people with dementia. Methods: An extensive review of the literature, including the Holy Qur’an, in several pertinent areas of inquiry that may deleniate the prevalence, potential risk factors related to dementia was under taken. Results: The overall prevalence of dementia for males and females doubled for every five years increase in age after the age of 65. It is largely a disease of older people. Results highlight a number risk factors associated with dementia. Inter alia, these include physical activities, education, occupation, stress, cholesterol and APOE gene. A number risk factors associated with dementia are modifiable. Conclusion: The prevalence of dementia rises as the people ages. The modifiable risk factors may have potential as strategies useful in preventing or delaying dementia among elderly subjects.